Trust and controlling = Zaufanie a controlling - Bieńkowska, Agnieszka; Zabłocka-Kluczka, Anna (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this study is to discuss the trust within and towards an organisation in the context of implementation of controlling therein. In this context the essence of trust and its importance in organisation management was presented, as well as trust in the contemporary management methods and concepts. Controlling as a trust-building factor inside an organisation was pointed out.
Keywords: organizacja; metody zarządzania; controlling; zaufanie; organization; management methods; trust